PALEOPRODUCTIVITY VARIATION AND ITS CORRELATION WITH CLIMATE CHANGES:AN APPROACH OF LONG-CHAIN ALKENONE - Nan, Q.; Li, T.; Chen, Jinxia; Yu, X.; Li, Q. (Quaternary Sciences, 2008)
The accurate reconstruction of paleoproductivity is critical for understanding the carbon cycle in the past and for predicting the fate of anthropogenic carbon in the future.Biomarkers in marine sediments are useful tools for paleoenvirionment study and have been used as proxies for total and specific phytoplankton group paleoproductivity.Based on 17 AMS14C age controlling points,we report here molecular abundance data for alkenone and organic carbon isotopic data for bulk samples from a giant piston core MD05-2908(24°48.04'N,122°29.35'E).The aim is to evaluate the paleoproductivity and interpret the climatic-induced controlling factors for the past 7000aB.P.The results showed that the paleoproductivity in the South Okinawa Trough(SOT)fluctuated frequently in the past 7000aB.P.By correlating with the Titanium records from Huguang Marr and Cariaco Basin,we found out that the paleoproductivity was largely controlled by the latitude migration of ITCZ.The rapid southward shift of the ITCZ might have caused longer staying of the rainfall front in the source supply area,thus,led to intensified erosion,brought increased terrigenous material into the ECS and SOT by fluvial the terrigenous materil delivers to the SOT.Terrigenous input on the one hand might have fertilized the sea surface of SOT and stimulated the production,but on the other hand might have diluted the signal of marine derived input to the sediments.The lower production periods in the SOT correlated well with those ice-drift episodes recorded in the high latitude Atlantic Ocean,suggesting the strong relationships between high and low latitude climate.
id: 1968
Keywords: Alkenone; ITCZ; paleoproductivity; SOT; the last 7000aB.P.

The Environmental Anomalies in the Northeastern East China Sea during the Last 3000 Years: Implications for El Nino Activity in the Holocene - Chang, F.; Zhuang, L.; Li, T.; Yan, J.; Li, Q. (9th International Conference on Paleoceanography (ICP 9), 2007)
id: 1935; TY: CPAPER; NO: Source type: conferencepapers&proceedings; Object type: Conference Paper; CSAUnique: CPI-4728602; AccNum: 4728602(China)
Keywords: Donghai Sea; Holocene; Multidisciplinary; Paleo studies; Paleoenvironments; U 7000